Biogenic Realgar As4S4 Molecular Clusters Formed by a One‐Pot Microbial‐Driven Process as a Li‐Ion Storage Material. (19th June 2017) - Kim, Tae‐Yang; Ahn, Hyungju; Jeon, Jeongsuk; Kim, Mi Sug; Kim, Min Gyu; Hur, Hor‐Gil
Abstract : Eco‐efficient biogenic strategies for the removal of toxic elements result in the formation of unique nano/microstructured materials with dual functionalities for energy conversion and storage. In one pot under aqueous conditions, the bacterium Shewanella sp. strain HN‐41 precipitates nanostructured arsenic sulfides (realgar, As4 S4 ) and its reduced graphene oxide nanocomposites. Considering the unique structural characteristics of the freestanding molecular‐cage‐like single clusters, the biogenic realgar structure is utilized as an independent anode unit since each cluster integrates four faceted five‐membered As4 S4 rings, providing a short diffusion length into each cluster and facile chemical binding onto the sulfur atoms with lone pairs of electrons. Here, the role of the biogenic realgar structure in the reversible uptake and release of Li ions into and from the molecular‐cage‐like single clusters is investigated. Using in situ As K‐edge X‐ray absorption fine structure analyses, the Li‐ion uptake ability of realgar As4 S4 (As4 S4 ↔Li20 As4 S4 ) is achieved through a two‐step mechanism: (1) molecular clustering to form Li8 As4 S4 (≈500 mA h g −1 ) and (2) alloying to form Li12 As4 only in the interior of the single clusters (≈750 mA h g −1 ). Thus, the bacteria‐driven biological synthesis under mild conditions can provide an alternative synthetic strategy and promotes easy scale‐up for nanostructured materials. Abstract : Eco‐efficient biogenic strategies with the Shewanella sp. strain HN‐41 bacetrium provide unique nanostructured arsenic sulfide (realgar, As4 S4 ) materials of free‐standing molecular‐cage‐like single clusters as an independent Li‐ion anode unit. This research, based on one‐pot facile microbiological synthesis under aqueous conditions without high energy‐consumption requirements, combines insights from biogeochemistry and energy conversion/storage materials science.